Effective Specific Heats of Multi-Phase Thermoelastic Composites - Chen, Y. Q.; Huang, R. C.; Huang, Z. P.; Sun, L. Z. (Acta Mechanica Solida Sinica, 2012)
This paper studies the effective properties of multi-phase thermoelastic composites. Based on the Helmholtz free energy and the Gibbs free energy of individual phases, the effective elastic tensor, thermal-expansion tensor, and specific heats of the multi-phase composites are derived by means of the volume average of free-energies of these phases. Particular emphasis is placed on the derivation of new analytical expressions of effective specific heats at constant-strain and constant-stress situations, in which a modified Eshelby's micromechanics theory is developed and the interaction between inclusions is considered. As an illustrative example, the analytical expression of the effective specific heat for a three-phase thermoelastic composite is presented.
Keywords: composite materials; effective specific heat; energy; free energy; matrix; micromechanics; models; thermoelasticity